Discovering Isozyme‐Selective Inhibitor Scaffolds of Human Carbonic Anhydrases Using Structural Alignment and De novo Drug Design Approaches. (26th December 2013) - Xiang, Fu; Xiang, Jun; Fang, Yuanping; Zhang, Mingju; Li, Maoteng
<x xml:space="preserve">Abstract</x> The development of isozyme‐selective carbonic anhydrase inhibitors is currently still a great challenge. In the present study, protein–ligand complex structures were obtained by AutoDock Vina with SBR ((R)‐N‐(3‐indol‐1‐yl‐2‐methyl‐propyl)‐4‐sulfamoyl‐benzamide) as the only inhibitor docked into the binding pockets of human isozymes CA I, II, IV, VI, IX, XII, and XIII. To make the spatial structures of complexes comparable, the co‐ordinates for CA domains were reassigned based on structural alignments. With preferred docking poses of SBR been reduced to seed structures, the LigBuilder was used to build up inhibitor molecules. The results suggested that sulfonamide derivatives with naphthalene, fluorene, and acridan as the scaffold structures can be the potential isozyme‐selective CAIs, especially for isozymes CA II, IV, and IX.